Outcomes of Percutaneous Nephrolithotripsy With or Without Nephrostomy Tube: A Comparative Study - Shrestha, Naresh Man (Journal of Nepalgunj Medical College, 2020)
Introduction: Percutaneous Nephrolithotripsy (PCNL) is one of the most accepted surgical modality for removal of renal stone. Placement of a nephrostomy tube at the end of PCNL is a standard procedure for PCNL, however many reports have showed the safety and efficacy of tubeless PCNL for the removal of renal stone. Aims: The present study aimed to report the outcomes of PCNL with or without nephrostomy tube. Methods: It is Prospective Hospital Study conducted from June 2017 to April 2020 in the Department of Urology Nepalgunj Medical College. Total 153 patients under inclusion criteria were divided into two groups. Group 1 (75 patients) was allocated to patients who were being treated under standard PCNL procedure while Group 2 (78 patients) was allocated for patients who were being treated under Tubeless PCNL procedure. The two groups were compared for operation time (minutes), hospital stay (days), post operative dose of analgesic (mg), post operative complications such as, leakage (%), bleeding (%) and infection (%). Data were analyzed from SPSS and p-value less than 0.5 was considered as significant. Results: In Group II the mean hospital stay, analgesic dose and rate of leakage was significantly lesser than Group I (p<0.05) whereas, the mean operation time, rate of infection and bleeding were not significantly different between two groups (p>0.05). Conclusion: Tubeless PCNL procedure causes more rapid recovery and earlier discharge from the hospital, reduction in postoperative pain and no leakage when compared to standard tubless PCNL.